2018
DOI: 10.1155/2018/5910342
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance Nurses’ Competence and Perception of Competence in Prehospital Trauma Care

Abstract: Introduction We focus on trauma care conducted in the context of a simulated traumatic event. This is in this study defined as a four-meter fall onto a hard surface, resulting in severe injuries to extremities in the form of bilateral open femur fractures, an open tibia fracture, and a closed pelvic fracture, all fractures bleeding extensively. Methods The simulated trauma care competence of 63 ambulance nurses in prehospital emergency care was quantitatively evaluated along with their perception of their suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…In this study, the overall prevalence of good knowledge was found to be 42.9% with 95%, CI (37.8–47.6). The finding was lower than the studies conducted in South Africa (51.7%), 21 Nepal (52%), 26 Sweden (71%), 27 Brazil (83.2%), 28 and Iran (72.2%). 29 The finding also lower than the studies done in Iran (61%), 30 India (69%), 23 and other two similar studies in India (48%), 13 and (52%) 25 of knowledge questions.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In this study, the overall prevalence of good knowledge was found to be 42.9% with 95%, CI (37.8–47.6). The finding was lower than the studies conducted in South Africa (51.7%), 21 Nepal (52%), 26 Sweden (71%), 27 Brazil (83.2%), 28 and Iran (72.2%). 29 The finding also lower than the studies done in Iran (61%), 30 India (69%), 23 and other two similar studies in India (48%), 13 and (52%) 25 of knowledge questions.…”
Section: Discussioncontrasting
confidence: 65%
“…43 The possible explanation might be due to the skill of an individual can improve the practice aspects of pre-hospital emergency care. 27 In a multivariable logistic regression analysis, variables like sex, marital status, educational level, experience, having training were found to have significantly associated with the practice of nurses in pre-hospital emergency nursing care. Being male was found to be nearly two times more to have good practice as compared with its counterparts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A basic condition for creating a structure for caring was performing a structured medical assessment as a fundamental dimension of the professional role, in which the students demonstrated varying levels of confidence in and preparedness for when entering their clinical practice (Studies I, II, III, IV). Performing advanced and structured medical assessments and deciding about medical treatment are identified as two of the most fundamental tasks defining the professional work of AS professionals [18,40,41,75,164,171]. As indicated by the findings in this thesis, the advanced medical assessment in the professional AS role is seen as requiring a competence that RNs need to further develop through further education, additional training, and clinical experiences to strengthen patient safety and professional security [40,172].…”
Section: Situational Awareness Task Load and Teamwork Processes In Dy...mentioning
confidence: 95%